Using Dependency Order Templates to Improve Generality in Translation - Menezes, Arul; Quirk, Chris (Proceedings of the Second Workshop on Statistical Machine Translation at ACL 2007, 2007)
Today's statistical machine translation systems generalize poorly to new domains. Even small shifts can cause precipitous drops in translation quality. Phrasal systems rely heavily, for both reordering and contextual translation, on long phrases that simply fail to match outof- domain text. Hierarchical systems attempt to generalize these phrases but their learned rules are subject to severe constraints. Syntactic systems can learn lexicalized and unlexicalized rules, but the joint modeling of lexical choice and reordering can narrow the applicability of learned rules. The treelet approach models reordering separately from lexical choice, using a discriminatively trained order model, which allows treelets to apply broadly, and has shown better generalization to new domains, but suffers a factorially large search space. We introduce a new reordering model based on dependency order templates, and show that it outperforms both phrasal and treelet systems on in-domain and out-of-domain text, while limiting the search space.